Ten years of English learning at school - Tragant, Elsa (Palgrave Macmillan, 2023)
This book is based on a longitudinal study involving learners of English as a foreign language from their first year in primary education to their last year in compulsory secondary education. Some of the chapters report on the whole sample initially drawn from five primary schools and some are based on a sample of focal learners. These focal learners were followed in secondary school (grades 7 and 10). One of the main aims of the book is capturing change over time regarding the learners’ language perceptions and awareness, oral and written language development, learners’ attitudes and motivation, and their language learning trajectories. The longitudinal nature of the data also allows identification of internal and external factors on learners’ linguistic outcomes. The book draws on a wealth of data sources (self-reported data, classroom observations, institutional data, language tests and tasks), participants (learners, teachers, parents), several testing times and both qualitative and quantitative analyses. The book will be of interest to educators and scholars working on such areas as language pedagogy, language development and awareness as well as individual differences.
9783031327582
Keywords: Hardcover; Softcover / Sprachwissenschaft; Literaturwissenschaft/Allgemeine und Vergleichende Sprachwissenschaft; Language and languages - Study and teaching; Inclusive education; Philology